Some psychometric characteristics of the officers’ perceived risk of simulated military operations scale - Ambrulaitienė, Giedrė (Psichologija, 2018)
This article presents the scale of the officers’ perceived risk of simulated military operations (hereinafter – the RPO). This methodology is based on a strategy of constructing empirical scales. The risk perceived by the officers in the article covers the internal convictions of junior officers regarding the risks of loss of life and property during simulated military tasks. The officers’ perceived risk scale would help in clarifying the structure of the perceived risks in the military and create conditions for revealing the sources of mistakes made during the military operations. With an identified relatedness between the most common decision-making mistakes and perceived risks among officers, we could carefully analyze the mistakes associated with the perceived risks of simulated military operations and contribute to reducing these errors by developing specific military training programs. The aim of this research is to develop a methodology for assessing the risks of a simulated military operation as perceived by the officers and to explore some of the psychometric characteristics of the said methodology. The research participants are officers of the Lithuanian Armed Forces from different counties of Lithuania. The research was conducted in three stages. In the first stage, 26 officers in total were involved, and a scale of 22 risky situations (the RPO scale) was compiled based on real-time observation and the semistructured interview method. The construction of risky situations was also based on theoretical assumptions and previous empirical researches in the fields of military, health and organizational psychology. In addition, during this stage of the study, the validity of the content of the completed scale was checked based on the assessments of an expert group. The second stage involved 94 officers. In this stage, the construct validity of the RPO scale was checked based on an analysis of cluster data and an expert group. In the third stage, data gathered from 129 officers were processed, and the construct validity of the RPO scale was checked. The RPO scale was prepared based on the study results of the three stages. The obtained results allow us to distinguish three subscales of the officers’ perceived risk scale of simulated military operations: the risk of civilian deaths, the risk of soldier and commander deaths, and the risk of the loss of resources and assets. The established psychometric characteristics of the RPO scale suggest that this scale is suitable for use in further research for assessing the risks perceived by officers in simulated military operations. This scale structure includes the key indicators of perceived risks relevant to the military process. Separate subscales of the created scale have sufficient internal compatibility (the Cronbach alpha coefficients: first subscale – 0.802; second subscale – 0.753; third subscale – 0.883). Also, the validity of the content of the RPO scale and the partial validity of the construct were verified.